Review of the concepts of action, omission and commission by omission: an analysis through cases (2017)
In this paper the different concepts of action, omission and commission by omission are studied. It is analysed whether this distinction is important or not, and the regulation contained in the Spanish Criminal Code is explained. Finally, these issues are